Aspectos ecológicos de tres escorpiones del piedemonte precordillerano de Mendoza - Roig Alsina, Arturo (Ecosur, 2025)
During a year was conducted a study about the scorpion community in the neighbourhoods of Mendoza, República Argentina. Sampling was carried out by means of dry pitfall traps with rock covers. TTie field study area was located about 20 kilometers west of the city of Mendoza on the Precordilleran foothill. This area is covered with the Larrea cuneifolia community. The habitat preference of each species is discused in relation to four microhabitats characterized by humidity. The population structure, reía ti ve abun dances and activity cycles are determined. The males emergences on the surface in spring are explosive and notably dephased in the three studied species.